Plant Pathology in India: Vision 2030 - IPS, Secretary (Indian Phytopathology, 2011)
In this book, a vision for the future of plant pathology has been described that must be pursued and supported for sustainable production of healthy plants upon which life itself depends.Â The Indian Phytopathological Society (IPS) recognizes the need to look to the future to best position the discipline to meet future societal needs and scientific opportunities.